Dark De/Re-Interpreters: predicative doubling in De Quincey and beyond. Issue 5 (28th May 2018) - Poutiainen, Hannu
ABSTRACT: The argument of this essay passes through the figure of the 'Dark Interpreter' in Thomas De Quincey's Suspiria de Profundis . Through an analysis of semantic, logical, ontological, and phenomenological issues pertaining to the concept of the double, which is defined here as the coexistence of two instances of the same singular entity, the essay examines the double as a locus through which the relation of existence to concept and of singularity to generality may be fundamentally rethought. Through readings of Edmund Husserl, Lubomir Doležel, Søren Kierkegaard, Jacques Derrida, Jorge Luis Borges, and Nicolas Abraham, the essay argues that the double, of which the Dark Interpreter is here the focal figure, emerges where the individuating predicate, the predicate which states what is unique and inimitable in a singular thing, takes on the function of the proper name. Following Derrida's analysis of the proper name, the essay demonstrates that the predicate, no longer simply belonging to the system of language, refers at once to several heterogeneous things, several doubles, whose radical nonequivalence disrupts and reconfigures the conceptual meaning of the predicate, thereby mixing, as De Quincey says of his oneiric double, the Dark Interpreter, with ever new alien natures.